The impact of COVID-19 in Ethiopia: brief - Harris, Donna; Baird, Sarah; Ford, Kath; Hirvonen, Kalle; Jones, Nicola (Oxford Management, 2021)
This brief examines the social and economic impacts of COVID-19 in Ethiopia so far, and suggests responses required to augment household welfare recovery and sustain poverty reduction.